A Novel Color Image Encryption Algorithm Based on Cross-plane Scrambling and Diffusion - Li, Xuejun; Sun, Bo; Bi, Xiuguo; Yan, Huizhen; Wang, Linian (Mobile networks and applications, 2024)
In this paper, a new color image cryptosystem with cross-plane scrambling and cross-plane DNA mutation diffusion is proposed. First, the plaintext image is processed by a secure hash algorithm(SHA) to obtain small perturbations, and then these perturbations are added to the parameters of the memristor chaotic system, which generates chaotic sequences and matrices according to the initial conditions and the new parameters. Secondly, in the scrambling process, the position information is first obtained from the chaotic matrix, and the pixels of the RGB channels of the color image are swapped. Then the position information generated by the chaotic sequences changes the position of each image pixel, respectively. In the diffusion process, the DNA operation is first executed on the scrambled image, and then each pixel value is changed by cross-plane DNA mutation diffusion. Finally, the security performance of the proposed cryptosystem is evaluated by various test methods. The experimental results demonstrate the effectiveness and security of the cryptosystem.